Problematika Pembelajaran Pendidikan Agama Islam Pada Siswa Slow Learnerdi SDN 04 Birugo - Mei Elvariani; Salmi Wati; Fauzan Fauzan; Nurhasnah Nurhasnah (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2024)
Researchers conducted research at SDN 04 Birugo based on the difficulty of slow learner students in understanding the lessons being taught. Slow learner children have difficulty reading so the tasks given by teachers to slow learner children cannot answer the tasks given by PAI teachers. This research aims to determine the problems of learning Islamic Religious Education among Slow Learner students at SDN 04 Birugo. This problem is researched using descriptive qualitative research methods which aim to describe and analyze phenomena and events, social activities, attitudes, beliefs, thoughts of people individually and in groups using field research. Data collection was carried out using observation, interviews and documentation techniques. The key informants in this research were the class IV Islamic Religious Education teacher at SDN 04 Birugo and the supporting informants for class IV slow learner students. To analyze the data, researchers grouped it based on existing problems. Based on the results of research conducted by researchers, the results show that slow learner students tend to feel inferior and consider themselves to be an obstacle to the learning process for other friends. Feelings of inferiority are seen in slow learner students at the stage of understanding lessons and completing assignments. There are two factors that cause difficulties in reading, writing and memorizing, namely the classroom environment and outside the classroom. Boredom occurs because they are not really serious about learning, but from the problems that occurred there were 3 slow learner students whose problems were slightly more resolved.